Human Capital and Economic Growth in OECD Countries - Torge Middendorf (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2005)
The results of the PISA 2000 study renewed the interest in the contribution of human capital to economic growth. So far the exploration of large country comparisons delivered rather mixed results. Concentrating on those OECD member countries which participated in PISA 2000, this paper uses panel data estimation techniques to refine this analysis. Estimation results reveal a positive impact of the human capital stock on economic growth suggesting that an increase in the average schooling years by one year yields a rise in the GDP growth rate of about 0.5 percentage points. However, when taking possible endogeneity into account in an instrumental variables approach, these conclusions on the impact of the level of human capital on economic growth is demonstrated to be rather fragile.
Keywords: I20; C23; O40; 330; Human capital accumulation; Convergence; Fixed-effects estimation; Instrumental variable estimation; Humankapital; Wirtschaftswachstum; Panel; Schätzung; OECD-Staaten